X+2x+(-5)=-11

Simple and best practice solution for X+2x+(-5)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+2x+(-5)=-11 equation:


Simplifying
X + 2x + (-5) = -11
X + 2x + -5 = -11

Reorder the terms:
-5 + X + 2x = -11

Solving
-5 + X + 2x = -11

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + X + 5 + 2x = -11 + 5

Reorder the terms:
-5 + 5 + X + 2x = -11 + 5

Combine like terms: -5 + 5 = 0
0 + X + 2x = -11 + 5
X + 2x = -11 + 5

Combine like terms: -11 + 5 = -6
X + 2x = -6

Add '-2x' to each side of the equation.
X + 2x + -2x = -6 + -2x

Combine like terms: 2x + -2x = 0
X + 0 = -6 + -2x
X = -6 + -2x

Simplifying
X = -6 + -2x

See similar equations:

| V=x(16-2x)(14-2x) | | 3(15-6)+(18-144)= | | 45=x(14-x) | | 3(s)=18 | | 2(x+1)(x-3)-(x+1)=0 | | x(x-6)-27=0 | | h=100t-16t^2 | | 2(2x+3)+1=11 | | 34(2*3)+45= | | -2f+3-2f-8= | | -2f+3-2f-8=-4f-5 | | 9.1x-6.5=x+2.7 | | 5(3-4y)=20 | | 12y-y+3= | | 11-2t=1 | | 5(y+4)=3 | | 7p+19=-2+55 | | 3s+2=-62 | | 6(x+2)-5=2x+4(2+x) | | 3y-1=32 | | 3x+25=4x | | 12-5(7+1)= | | 4*-1-2= | | y=5+2(3-4x) | | 13.2+x=61-48.9 | | 3n=50+5n | | 4x+10=6x | | 2y+7=5y-2 | | y=5+2(3+4x) | | 7p+10=2p+55 | | (5x+2y)+(5x+y)= | | (4+x)-(2+x)= |

Equations solver categories